”Hvoraf kommer det, at vi alle ere saa demokratiske som vi ere?” - Demokratisk-monarkiske bondevenner i den danske grundlovskamp - Nørgaard, Anne Engelst (Slagmark - Tidsskrift for idéhistorie, 2018)
The article studies the rhetoric of ’Bondevennernes Selskab’, an organized peasant movement, in the constitutional battle of 1848-49. Through an analysis of speeches held on the constitutional assembly by members of the peasant movement, the article concludes that the movement’s call for democracy was supported with a rhetoric that used the absolutist king as a legitimizing figure. Through the principle of popular sovereignty, the concept of democracy was connected to the concept of ‘people’ and ideas of a strong monarch. This rhetoric was used to legitimize the status of the peasant movement as speaking on behalf of the people and in claiming political agency for the peasantry.